Effect of Soil Application with Trichoderma harzianum and Some Selected Soil Amendments on Fusarium Wilt of Tomato - Islam, M. T.; Faruq, A. N.; Uddin, M. M.; Akhtar, N. (International Journal of Bio-resource and Stress Management, 2010)
Field experiments were carried out to test the efficacy of Trichoderma harzianum and some selected soil amendments such as poultry waste, coco-dust, vermicompost, ash, saw-dust, khudepana, cow dung, solarized sand, etc. against wilt disease of tomato during the winter season of 2008-2009. The treatments were applied in the soil at 15 days before transplanting. It was found that all the treatments appreciably reduced wilt incidence at different days after transplanting. In general, the wilt incidence was higher on control plot where no treatments were used. The most effective treatment was Trichoderma harzianum followed by poultry waste in terms of suppressing wilt incidence, increasing plant growth and fruit yield. Vermicompost also showed better performance in suppressing the wilt incidence at different days after transplanting over control and enhancing the plant growth and fruit yield.